The typology of semantic alignment - Donohue, Mark, 1967-; d (Oxford : Oxford University Press, 2008)
Leading scholars explore the characteristics of languages with semantic alignment systems and compare the structure of languages with and without them, with special reference to Eurasia, the Americas, and the south-west Pacific, where semantically aligned languages are concentrated.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Semantics; Typology (Linguistics)